EFFECT OF LEMON AROMATHERAPY ON THE ANXIETY LEVEL OF DENTAL EXTRACTION PATIENTS IN RSND SEMARANG - Hayuratri Purwalalita Laksmidevi; Devi Farida Utami; Arinta Puspita Wati; Maria Belladonna Rahmawati (Jurnal Kedokteran Diponegoro, 2021)
Background: Dental treatment that is often done is the tooth extraction procedure. The treatment and the use of sharp instruments such as syringes, pliers, bein during extraction can cause anxiety. Anxiety will be responded by several changes in the body such as the increasing of MAP, pulse rate, and respiratory rate. Handling anxiety can be done with aromatherapy, one is lemon aromatherapy.